a,x-36:18=12
\(\Rightarrow\)x-2=12
\(\Rightarrow\)x=12+2
\(\Rightarrow\)x=14
b,(x-36):18=12
\(\Rightarrow\)x-36=18.12
\(\Rightarrow\)x-36=216
\(\Rightarrow\)x=216+36
\(\Rightarrow\)x=252
\(x-36:18=12\)
\(x-2=12\)
\(x=12+2\)
\(x=14\)
\(\left(x-36\right):18=12\)
\(\left(x-36\right)=12\times18\)
\(x-36=216\)
\(x=216+36\)
\(x=252\)
a) x - 36 : 18 = 12
x - 36 = 12 x 18
x - 36 = 216
x = 216 + 36
x = 252
b) ( x - 36 ) : 18 = 12
x - 36 = 12 x 18
x - 36 = 216
x = 216 + 36
x = 252
a) x - 36 : 18 = 12
x - 2 = 12
x = 12 + 2
x = 24
b) ( x - 36 ) : 18 = 12
x - 36 = 12 x 18
x - 36 = 216
x = 216 +36
x = 252
a) x - 36 : 18 = 12
x - 2 = 12
x = 12 + 2
x = 14
b) ( x - 36 ) : 18 = 12
x - 36 = 12 x 18
x - 36 = 216
x = 216 + 36
x = 252
x-2=12
x=12+2=14
(x-36):18=12
(x-36) =216
x-36 =216
x=216+36=252
a, x - 36 : 18 = 12 b, ( x - 36) : 18 = 12 x - 2 = 12 x - 36 = 12 x 18 x = 12 + 2 x - 36 = 216 x = 14 x = 216 + 36 x = 252
a) x-36:18=12 x -16 =12*18 x-36 =216 x =216+36 x =252 câu b) tương tự bài trên